TEAMWORK OF THE DIRECTORS IN CHONBURI PRIMARY EDUCATINAL SERVICE AREA OFFICE - ศิลาสุวรรณ พัสวีพิชญ์ (Pathumthani University Academic Journal, 2020)
The sample who answered this questionnaire consisted of 360 teachers working in the Chonburi Primary Educational Service Area Office. The key informants for the in-dept interview were composed of 6 school administrators. The instruments employed 5-rating scale questionnaire and interview form. The statistics for data analysis were frequency, percentage, mean, standard deviation, and content analysis. The major finding revealed that 1) The teamwork of the school administrators in Chonburi Primary Educational Service Area Office was at a high level. 2) The teamwork guidelines of communication of the school administrators in Chonburi Primary Educational Service Area Office, the school administrators have guidelines for management by arranging the teachers meeting every month to give the opportunity for school administrators to explain details of each other’s doubts with clear language. Teachers could make inquiries directly through all communication channels, such as via personality, technology, collaboration. School administrators have guidelines for management by considering that the school administration should be a management from many departments, so that the teachers have various concepts with power to make decision in working and individualized consultation. As for coordination, school administrators have guidelines for management that the school executives should give priority to the hierarchal coordination between departments. The supervisor’s hierarchy was clear and straightforward with meaning in the used language content. In the field of creativity, school administrators provided ideas without too uncomfortable frame to work. As for the continuous improvement, school administrators should observe behavior and learn the characteristics of subordinates to select the problem and specify the problem clearly, to analyze problems and causes, and to find root causes that the teachers confronted.